Mode, the hub of multimodality: A case study of Oral-B® Toothpaste advertising - Dalamu, Taofeek Olaiwola (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
This study investigates the nature of modal constructs in advertising commercial, operational in Oral-B® Toothpaste, to explain the mechanistic integration of modes, unified to generate holistic meaning. With the application of the mood system and kinesics concepts, the author is able to interpret the video for readers. Besides using statistical substances (tables and graphs) to explore the modes, one observes a fragmentation of structures of some linguistic items such as The answer?, Easy, still fresh and strong. Repetition is a concern, where the communicator deploys the generic You, your teeth, and your mouth for a reason of emphasis. Communicative devices such as strong and healthy, and long lasting fresh breath (feeling) are details, exemplifying the Oral-B’s 2-IN-1 qualities. Gestural modes of smiling, observed in a repetitive speeches of Smile, Smile, Smile, and intimate and personal distances augment meanings as Social Actors 1 and 2 are indexical participants. Metaphorical professional actors and the dual 2-IN-1 features characterize the communication, projecting interchangeability. The advertisement is fascinating; yet, the metaphor of interchangeability could have been simplified for a purpose of sensitizing the illiterate.